Nyeri Punggung Bawah Akibat Posisi Duduk yang Salah Pada Pesepeda - Zahra Salsabila Hafid; Ummy Aisyah N; Parmono Dwi Putro (Jurnal Keterapian Fisik, 2020)
Background: Lower back pain still occurs in many cyclists. The sitting position is considered to be one of the factors causing complaints of low back pain. This study was conducted to determine the correlation between sitting position and complaints of low back pain in cyclists. Methods: This study employed the narrative review method by collecting ten research articles from the Google Scholar and PubMed databases, identifying keywords using the PEOs format, so that the keywords "Cyclist", "Sitting Position", "Lower Back Pain", and "All Study Design" were used. Results: All articles used were articles published starting in 2010. Seven articles stated that lower back pain occurred more frequently in a sitting position with large lumbar flexion. Six articles stated that the sitting position of a cyclist was affected by the position of the handlebars. Five articles stated that sitting with the lower handlebars resulted in greater lumbar flexion and anterior pelvic tilt. Five articles stated that prolonged lumbar flexion and anterior pelvic tilt resulted in a lower crossed syndrome. Four articles found that lower crossed syndrome contributes to lower back pain. Conclusion: There is a correlation between sitting position and complaints of low back pain in cyclists. However, there are limitations to the article which states that the statistical closeness of the correlation between sitting position and complaints of low back pain in cyclists.